Chemical Composition of Paddy Straw as Affected by Treatment with Maize Spent Liquor - 1,; 1,; 1,; 2, (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The experiment was conducted to study the chemical composition of untreated paddy straw and that treated with Maize spent liquor(MSL) at varying levels (10, 20 and 30 %) and incubated for one day. The DM, OM, TA, CP, EE, CF, NFE, Ca and P content of Maize spentliquor (MSL) were 16.88, 91.96, 8.04, 14.33, 4.37, 0.00, 73.26, 0.24 and 0.69%, respectively. Higher (p
Keywords: Chemical composition; Inclusion level; Maize spent liquor; Paddy straw